2011
DOI: 10.1002/jctb.2650
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic reactors for environmental remediation: a review

Abstract: Research in the field of photocatalytic reactors in the past three decades has been an area of extensive and diverse activity with an extensive range of suspended and fixed film photocatalyst configurations being reported. The key considerations for photocatalytic reactors, however, remain the same; effective mass transfer of pollutants to the photocatalyst surface and effective deployments and illumination of the photocatalyst. Photocatalytic reactors have the potential versatility to be applied to the remedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
178
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(179 citation statements)
references
References 111 publications
0
178
0
1
Order By: Relevance
“…However, their application is a matter of discussion. Moreover, the application of semiconductors in photocatalysis for remediation has real scope for impacting water pollution and, hence, global water scarcity (McCullagh et al 2011). Adams et al (2008) have reported the comparison of a standard flat plate reactor with a novel drum reactor (Robertson et al 2004) for the removal of organic (oil and gas hydrocarbons) contaminants from the water.…”
Section: Titanium In the Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, their application is a matter of discussion. Moreover, the application of semiconductors in photocatalysis for remediation has real scope for impacting water pollution and, hence, global water scarcity (McCullagh et al 2011). Adams et al (2008) have reported the comparison of a standard flat plate reactor with a novel drum reactor (Robertson et al 2004) for the removal of organic (oil and gas hydrocarbons) contaminants from the water.…”
Section: Titanium In the Industrymentioning
confidence: 99%
“…Such a high level of reduction over a short period of time is attributed to samples passing through 3 consecutive drums, each with 200 g of TiO 2 catalyst present. Therefore, 600 g of catalyst are utilized for the entire system (Adams et al 2008, McCullagh et al 2011. It is important to understand that there is no sense in applying these kinds of catalysts in doses exceeding those confirmed effective by research.…”
Section: Titanium In the Industrymentioning
confidence: 99%
“…In order to fully assess the potential of photocatalysis as a water purification method, consideration needs to be given to the reactor unit in which the photocatalyst is deployed. There are a number of issues that need to be considered when designing a reactor to be employed for the photocatalytic purification of water [2]. A key parameter influencing the water treatment capability of the photocatalytic reactor is the quantity of catalyst that can be activated [3].…”
Section: Photocatalytic Water Treatmentmentioning
confidence: 99%
“…Therefore, many types of photocatalytic reactors have been designed for water treatment, but they are still facing enormous challenge and difficulties. [1][2][3][4] Microfluidics may find potential uses for photocatalysis but such application area remains merely a virgin land until recently. [5][6][7] The great success of microfluidics in many applications such as chemical analysis, biomedical assay, and drug screening has well demonstrated its remarkable capabilities in dealing with particles, fluids, and light in an integrated platform.…”
Section: Introductionmentioning
confidence: 99%